Structural stability, electronic and optical properties of MAX-phase ternary nitrides β-TM4AlN3 (TM = V, Nb, and Ta) using the first-principles explorations. (November 2021) - Lu, Yaoping; Yang, Ancang; Duan, Yonghua; Peng, Mingjun
Abstract: To explore the scope of application and provide theoretical guidance for the synthesis of MAX-phase β-TM4 AlN3 (TM = V, Nb, Ta) ternary nitrides, the first-principles calculations based on density functional theory were performed, and the phase stability, electronic structures and optical properties of these nitrides were predicted. The formation enthalpies of V4 AlN3, Nb4 AlN3 and Ta4 AlN3 were −4.030, −4.065 and −4.048 eV/atom, respectively, indicating that they exhibit structural stability. The results of electronic structures indicated that these nitrides are metallic and V4 AlN3 should have a higher electroconductibility than other two nitrides. Based on the predicted optical properties, the applications of β-TM4 AlN3 (TM = V, Nb, Ta) ternary nitrides were discussed. Moreover, Ta4 AlN3 has the highest optical anisotropy and Nb4 AlN3 exhibits the least optical anisotropy. Highlights: Nb4 AlN3 is the most stable compared to V4 AlN3 and Ta4 AlN3 . The order of optical anisotropy is Ta4 AlN3 > V4 AlN3 > Nb4 AlN3 . V4 AlN3, Nb4 AlN3, and Ta4 AlN3 have potential in optical shielding materials.